Geographical Impact on the Cognitions of New Factory Workers: A Comparative Factor Analysis - Klein, Stuart M. (Academy of Management Journal, 1973)
The purpose of this research was to identify geographical contingencies that might affect the generalizations of prescriptive organizational theories. Two matched though geographically disparate factory populations, one from the Southeast and one from the Midwest, were compared on factor structure and factor similarity. It was found that clear differences obtained in the way each of these groups of new workers ordered their cognitions concerning their factory experience.